The potential of neutrophil gelatinase-associated lipocalin in management of acute kidney injury and peritoneal dialysis-related peritonitis: a narrative review - Fu, Xiao; Shu, Yiting; Zhang, Yun (Frontiers in Nephrology, 2026)
Neutrophil gelatinase-associated lipocalin (NGAL) is a biomarker extensively studied in multiple diseases. While its application in chronic kidney disease (CKD) and kidney transplant patients is relatively limited, NGAL has shown significant promise in the early detection and diagnosis of acute kidney injury (AKI), which may improve more timely management and potentially better clinical outcomes. In addition, NGAL has demonstrated promising utility in identifying peritoneal dialysis-related peritonitis (PDRP) and monitoring the treatment response. This review aims to provide an in-depth overview of the available research findings of NGAL in the management of AKI and PDRP, having these two conditions discussed together is particularly important for nephrologists who manage both conditions, especially to explore the potential of more specific NGAL forms, such as monomer NGAL and homodimer NGAL, to enhance early diagnosis and effective management of AKI and PDRP.